Solvothermal synthesis and photocatalytic performance of Mg2+-doped anatase nanocrystals with exposed {0 0 1} facets - Sofianos, Veronica; Tassi, M.; Boukos, N.; Thanos, S.; Vaimakis, T.; Yu, J.; Trapalis, C. (Elsevier BV, 2014)
The photocatalytic activity of TiO2 and magnesium doped TiO 2 nanocrystals in dopant range of 2-6.2 at%, was studied. The doped and undoped nanocrystals with exposed {0 0 1} crystal facets were synthesized by a solvothermal method. Several studies have shown that the (0 0 1) surface of the TiO2 anatase crystal is more reactive than the thermodynamically stable (1 0 1) surface. The crystal structure as well as the shape of the TiO2 and Mg2+/TiO2 anatase nanoparticles were determined using two different techniques, such as X-ray powder diffraction (XRD) and transmission electron microscopy (TEM), which both lead to the agreeable conclusion that the nanocrystals are in the form of plates. Chemical analysis of the photocatalyst was carried out with X-ray photoelectron spectroscopy (XPS) and showed the presence of magnesium ions in the TiO 2 nanoplates. UV-vis diffuse reflectance spectroscopy (DRS) showed that there is an adsorption shift for doped TiO2 to visible light region. The photocalaytic efficiency of the synthesized catalysts was investigated by the photocatalytic oxidation of the gaseous nitric oxide (NO) and decomposition of the gaseous acetaldehyde (CH3CHO) under UV irradiation. It was demonstrated that the low Mg2+ doped catalysts exhibited higher photocatalytic activity than the pure TiO2. The optimal concentration of dopant that is beneficial for the photocatalytic activity was studied. © 2013 Elsevier B.V.